Understanding Our Being : Introduction to Speculative Philosophy in the Perennial Tradition - Carlson, John W. (Book collections on Project MUSE., 2008)
"In the encyclical Fides et ratio, Pope John Paul II called upon teachers of philosophy "to recover, in the flow of an enduringly valid philosophical tradition, the range of authentic wisdom and truth." Understanding Our Being responds to this call with an introduction to speculative philosophy. It treats central topics about our knowledge of being, the being of the natural world, and, via the latter, being as such. It then treats the special character and implications of our human, personal being - in particular, our intellect, free choice, and reason-conditioned sociality. Finally, it considers God as Source and End of being and it discusses the "problem of evil" and the nature of religious faith."--Jacket